Cromo (VI) na solução do solo e fitotoxicidade em plantas de alface, feijão, milho e soja - Reis, Rayner Hugo Cassa Louzada dos (2019)
Soil provides many essential ecosystem services to maintain the quality and healthy development of flora, fauna and human well-being. The contamination of soils by heavy metals from anthropogenic activities has become a very serious environmental problem in many countries. The assessment of toxicity caused by a chemical substance in the environment is one of the interesting alternatives in the contamination scenario. Hexavalent chromium [Cr(VI)] is considered an environmental pollutant and is found in leather processing and electroplating industries, stainless steel manufacturing, tanning effluents. Its inadequate and uncontrolled discharge contaminates the soil and water. The concentration of Cr (VI) in soil solution harmful to growth and deleterious effects in different plants were evaluated. In order to achieve this objective, lettuce, beans, maize and soya were grown to evaluate phytotoxicity after exposure to five different concentrations of Cr (VI): 0, 8, 80, 160, 320 mg kg-1 of dry soil using K2Cr2O7. Soil solutions of a red distropheric latosol with clayey texture were analysed using UV/Vis molecular absorption spectrometry based on the diphenylcarbazide method for Cr(VI). Growth measurements were performed. Corn was the most sensitive species for height and aerial biomass at the end of the experiment, while lettuce and soybeans were shown to be the species less sensitive to Cr (VI). More Cr (VI) was found in the soil solution following lettuce > beans > soybeans > maize.